Propuesta de departamento de mantenimiento para una cooperativa del sector agroindustrial - Cortés-Cascante, Maureen Johanna (Instituto Tecnológico de Costa Rica, 2016)
This document presents an evaluation of the Maintenance Management by applying the COVENIN 2500-93 standard, in order to determinate the current state of the maintenance organization in APACOOP R.L. This standard is a guideline for the evaluation of the most important aspects related to the maintenance of the organization and thereby making the proposal relevant. The main proposal is to make the bases for the implementation of a Maintenance Department in the cooperative, since this make by outsourcing those activities. To this it proposes an Initial Maintenance Management Model and it develops some of the key aspects that this cover. This model is based on preventive maintenance of critical equipment in order to avoid unscheduled stops. The activities of this preventive maintenance are proposed for those selected equipment through a criticality analysis. In addition, plans are proposed to make an autonomous maintenance for equipment that may be subject to this kind of maintenance. On the other hand, important aspects are established for the organization of this Maintenance Department. Furthermore, in this writing are designed the required administrative documents and flowcharts for each of them with organization context propose for the company. Also it is designed a database to facilitate the processing of generated data during the operation of the projected department. Maintenance indicators are established that are appropriate to the operative environment of the company to measure the performance of this proposed department and to make them a base for decision making and for the process of continuous improvement on it. Key words: Maintenance Department, Preventive Maintenance Management, Autonomous Maintenance, Maintenance Indicators, Maintenance Procedure and Document.

En este trabajo se realiza una evaluación de la Gestión de Mantenimiento mediante la aplicación de la norma COVENIN 2500-93, con el fin de determinar el estado actual de la organización del mantenimiento en APACOOP R.L. Esta norma es un manual para la evaluación de los aspectos más importantes de la organización relacionados con el mantenimiento y con ello realizar las propuestas pertinentes. Se realiza la propuesta de las bases para la implantación de un Departamento de Mantenimiento en la cooperativa, ya que esta realiza las actividades de mantenimiento mediante tercerización. Para ello se plantea un Modelo Inicial de Gestión de Mantenimiento y se desarrolla algunos de los aspectos que este contempla. Dicho modelo se basa en el mantenimiento preventivo de los equipos críticos con el fin de evitar paradas no programadas. Las actividades de mantenimiento preventivo se proponen para los equipos seleccionados mediante un análisis de criticidad. Además, se proponen planes de mantenimiento autónomo para equipos que pueden ser sujetos de este tipo de mantenimiento. Por otro lado, se establecen aspectos importantes en lo que se refiere a la organización del Departamento de Mantenimiento. Además, se diseñan los documentos administrativos requeridos y los diagramas de flujo para cada uno de ellos en el contexto organizacional propuesto para la cooperativa. Se diseña también una base de datos que facilite el procesamiento de los datos generados durante la operación del departamento proyectado. Se establecen indicadores de mantenimiento que se adapten al contexto operativo de la empresa, que permitan medir el desempeño del departamento y sirvan como base para la toma de decisiones y para el proceso de mejora continua en él.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2016.
Keywords: Mantenimiento; Gestión; Mantenimiento preventivo